Analisis Kemampuan Peserta Didik SMP Negeri 1 Makassar dalam Mengoperasikan Angka Penting - Nur Amalia Rezkyani; Salma Samputri; Muh. Tawil (Universitas Negeri Makassar, 2025)
This research is a quantitative descriptive survey research that aims to describe students' ability to operate significant figures in SMP Negeri 1 Makassar. The population of this study were all students of class VII SMP Negeri 1 Makassar totaling 448 students. The sample of this research is 448 which uses saturated sample technique. The research instrument consisted of multiple choice questions, 10 question numbers to test the ability to operate significant. Based on data analysis it is known that the ability level of SMP Negeri 1 Makassar students in operating significant figures is in the medium category with a percentage of 57.6%.